(untitled) (Colombia Medica, 2014)
Objectives: To determine the frequency, variability, sexual dimorphism and bilateral symmetry of fourteen dental crown traits in the deciduous and permanent dentition of 60 dental models (35 women and 25 men) obtained from a native, indigenous group of Nasa school children of the Musse Ukue group in the municipality of Morales, Department of Cauca, Colombia. Methods: This is a quantitative descriptive, cross-sectional study that characterizes dental morphology by means of the systems for temporary dentition from Dahlberg (winging), and ASUDAS (crowding, reduction of hypocone, metaconule and cusp 6), Hanihara (central and lateral incisors in shovel-shape and cusp 7), Sciulli (double bit, layered fold protostylid, cusp pattern and cusp number) and Grine (Carabelli trait); and in permanent dentition from ASUDAS (Winging, crowding, central and lateral incisors in shovel-shape and double shovel-shape, Carabelli trait, hypocone reduction, metaconule, cusp pattern, cusp number, layered fold protostylid, cusp 6 and cusp 7). Results: The most frequent dental crown features were the shovel-shaped form, grooved and fossa forms of the Carabelli trait, metaconule, cusp pattern Y6, layered fold, protostylid (point P) and cusp 6. Sexual dimorphism was not observed and there was bilateral symmetry in the expression of these features. Conclusions: The sample studied presented a great affinity with ethnic groups belonging to the Mongoloid Dental Complex due to the frequency (expression) and variability (gradation) of the tooth crown traits, upper incisors, the Carabelli trait, the protostylid, cusp 6 and cusp 7. The influence of the Caucasoide Dental Complex associated with ethno-historical processes cannot be ruled out.